The Effect of Sharia and Religiosity Labels on Community Interests Using Sharia Banking - Ema Elisa; Samsul Hidayat (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
This research is motivated by the problems that the researchers found, which there are still many Muslim communities in Pontianak city prefer to use conventional banks rather than sharia banks. The lack of interest in the Muslim community to use syaria banks is due to many factors including the sharia label and religiosity. This study aims to determine the effect of the sharia label and religiosity on people's interest in using Islamic banks. The sample size in this study uses the Lemeshow formula, this was because the population size was unknown. The data used in this study were primary data obtained through questionnaires distributed to the Muslim community in Pontianak City in 2023. Based on a sample of 100 respondents using multiple linear regression analysis, the results of this study indicated that the label sharia and religiosity have a positive effect and giving significance to the interest in becoming a customer of sharia banks. The results of this study also showed that the Sharia Label and Religiosity have a simultaneous effect on Public Interest in Using Sharia Banks.